Comparison the training methods of neural network for English and Thai character recognition - Anakkapon Saenthon; Natchanon Sukkhadamrongrak (My University, 2014)
Currently, the optical character recognition (OCR) is applied in many fields such as reading the office letter and to read the serial on parts of industrial. The most manufacturing focus the processing time and accuracy for inspection process. The learning method of the optical character recognition is used a neural network to recognize the fonts and correlation the matching value. The neural network has many learning techniques which each technique impact to the processing time and accuracy. Therefore, this paper studies to comparisons a suitable procedure of training in neural network for recognizing both Thai and English characters. The experiment results show the comparing values of error and processing time of each training technique.
Keywords: Optical character recognition; Neocognitron; Neural Networks and Applications